Nurses’ attitude towards communication with intubated conscious patients: an online survey - Karmakar, Mahuya; Said, Faridah Mohd; Panduragan, Santhna Letchmi (Intelektual Pustaka Media Utama, 2025)
The lack of communication causes dissatisfaction and distress among conscious intubated patients, which may result in treatment refusal. This preliminary study sought to identify attitudes of nurses towards communication with conscious intubated patients. Thus, possible solutions to improve the communication challenges if exist by finding the attitude of nurses on communication with conscious intubated patients may be explored. Preliminary survey was conducted among selected nurses through convenient sampling method. Questionnaire self-developed, validated were distributed and analyzed descriptively. Almost all respondents believed that conscious patients do want to communicate during intubated period and eighty two percent of the respondents agreed that communication with conscious intubated patients is possible. Seventy five percent respondents have tried to communicate using both verbal and non-verbal methods but 70% have faced challenges. Though only thirty seven percent of the respondents have been taught how to communicate with the intubated conscious patients, sixty four percent of respondents have never asked for any tools for communication. To overcome the communication challenges majority 103 (82.4%) of the respondents stated the requirement of standardized communication tool. The result indicates a need to develop standardized communication tool to ease communication with conscious intubated patients.